Fish skeletal muscle tissue is an important focus of immune reactions during pathogen infection. (August 2017) - Valenzuela, Cristián A.; Zuloaga, Rodrigo; Poblete-Morales, Matías; Vera-Tobar, Tamara; Mercado, Luis; Avendaño-Herrera, Ruben; Valdés, Juan Antonio; Molina, Alfredo
Abstract: Skeletal muscle in mammals can express and secrete immune-related molecules during pathogen infection. Despite in fish is known that classical immune tissues participate in innate immunity, the role of skeletal muscle in this function is poorly understood. To determine the immunocompetence of fish skeletal muscle, juvenile fine flounder ( Paralichthys adpersus ) were challenged with Vibrio ordalii . Different Toll-like receptors, pro-inflammatory cytokines (TNFα, Il-1β, and IL-8), and immune-effector molecules (NKEF and the antimicrobial peptides hepcidin and LEAP-2) were analyzed. Infection initially triggered IL-1β upregulation and P38-MAPK/AP-1 pathway activation. Next, the NFĸB pathway was activated, together with an upregulation of intracellular Toll-like receptor expressions ( tlr3, tlr8a tlr9, and tlr21 ), TNFα production, and leap-2 expression. Finally, transcriptions of il-1β, il-8, tnfα, nkef-a, and hepcidin were also upregulated. These results suggest that fish skeletal muscle is an immunologically active organ that could play an important role against pathogens. Highlights: V. ordalii infection trigger expression changes of immune-related genes in fish muscle. Skeletal muscle response against V. ordalii depends on intracellular TLRs. The muscle tissue is able to express antimicrobial peptides in response to infection.